1976
DOI: 10.1073/pnas.73.4.1203
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on pro-leu-gly-nh2 conformation.

Abstract: Classical potential function calculations were carried out on the hypothalamic factor Pro-Leu-Gly-NH2. The results indicate that the proposed 1O-membered, hydrogen-bonded f-turn conformation of this tripeptide is a strongly preferred structure. Its stability appears to be inherent in the rather rigid backbone conformation of the leucine residue rather than the hydrogen bond between the carboxamide proton of glycinamide and the C=O of the proline moiety; the glycinamide has little influence on the 04 of the leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A comparison of the conformations of dipeptide segments in the X-ray structures of 20 globular proteins with the calculated conformations of isolated dipeptides of the same amino acid sequences suggested that, for many dipeptide sequences in proteins, /?-bends are stabilized mainly by local interactions (Zimmerman et al 1977b). Ralston, De Coen & Walter (1974), Kang & Walter (1976), and Zimmerman & Scheraga (1977c) used energy calculations to determine stable conformations of H-Pro-L-Leu-Gly-NH 2 , the melanotropin release inhibiting factor. All three studies showed that a type II /?-bend was a low-energy structure, in agreement with the proposed structure in dimethylsulphoxide (Walter, Bernal & Johnson 1972) and with the X-ray crystal structure (Reed & Johnson, 1973).…”
Section: Calculationsmentioning
confidence: 99%
“…A comparison of the conformations of dipeptide segments in the X-ray structures of 20 globular proteins with the calculated conformations of isolated dipeptides of the same amino acid sequences suggested that, for many dipeptide sequences in proteins, /?-bends are stabilized mainly by local interactions (Zimmerman et al 1977b). Ralston, De Coen & Walter (1974), Kang & Walter (1976), and Zimmerman & Scheraga (1977c) used energy calculations to determine stable conformations of H-Pro-L-Leu-Gly-NH 2 , the melanotropin release inhibiting factor. All three studies showed that a type II /?-bend was a low-energy structure, in agreement with the proposed structure in dimethylsulphoxide (Walter, Bernal & Johnson 1972) and with the X-ray crystal structure (Reed & Johnson, 1973).…”
Section: Calculationsmentioning
confidence: 99%
“…]amino]-2-oxo-1-piperidineacetamide (19). Boc-L-Pro-OH (1.37 g, 6.36 mmol) and lactam 18 (1.32 g, 6.36 mmol) were dissolved in DMF (10 mL), and the resulting solution was cooled to 0 °C.…”
Section: (S)-[[lv-(tert-butoxycarbonyl)-l-prolylmentioning
confidence: 99%